Elaborating Islamic Educational Values in the Nussa and Rara Series for Early Childhood: The Episode "Makan Jangan Asal Makan" - Usrah, Ayyada; Sabani, Fatmaridah; Mahmudah BuluÔÇÖ, Rifa'ah (Journal of Islamic Education Students (JIES), 2025)
Instilling religious values from an early age is essential in shaping childrenÔÇÖs moral and spiritual character. The Nussa and Rara animated series serves as an engaging educational medium for young audiences. This study aims to explore the Islamic educational values presented in the episode ÔÇ£DonÔÇÖt Eat CarelesslyÔÇØ and examine its implications for early childhood education. A descriptive qualitative method with content analysis was employed. The results reveal the presence of aqidah values (faith in Allah as the provider), ibadah values (reciting basmalah, eating with the right hand, drinking in three sips), and akhlaq values (maintaining health, etiquette, and cleanliness). These values are delivered through songs and visuals that are appealing and easily understood by young children. The findings suggest that religious-themed animations like Nussa and Rara can serve as effective alternative media for Islamic character education. They also support their use by educators and parents as supplementary learning tools in early childhood education settings.┬á